The false prince - Nielsen, Jennifer A. (New York : Scholastic Press, 2012)
In the country of Carthya, a devious nobleman engages four orphans in a brutal competition to be selected to impersonate the king's long-missing son in an effort to avoid a civil war.
710
MSBA nominee 2013-14.
Keywords: Impersonation -- Juvenile fiction; Princes -- Juvenile fiction; Orphans -- Juvenile fiction; Courts and courtiers -- Juvenile fiction; Secrecy -- Juvenile fiction; Fantasy fiction